Prevalence, Risk Factors and Effects of Domestic Violence Before and During Pregnancy on Birth Outcomes: An Observational Study of Literate Omani Women - Al Shidhani NA; Al Kendi AA; Al Kiyumi MH (Dove Medical Press, 2020)
Nuhour Ali Al Shidhani,1 Asma Ali Al Kendi,1 Maisa Hamed Al Kiyumi2 1Ministry of Health, Muscat, Oman; 2Department of Family Medicine and Public Health, Sultan Qaboos University Hospital, Muscat, OmanCorrespondence: Maisa Hamed Al KiyumiSultan Qaboos University Hospital, P.O.Box 35, P.C.123, Al-Khod, Sultanate of OmanTel +0096824141127Email maysa8172@gmail.comBackground: Domestic violence against women before and/or during pregnancy is a concerning public health issue. It has a deleterious impact on both the mother and the baby.Aim: The aim of this study is to identify the prevalence and predictors of emotional and physical domestic violence during three periods (lifelong, one year before pregnancy and during pregnancy). Moreover, it evaluates the effects of domestic violence on the outcomes of pregnancy, including miscarriages, birth weight of the baby, gestational age at delivery, and mode of delivery.Methodology: This is a prospective observational study of literate pregnant women, attending four primary health-care centers in Muscat, from 1st April 2019 to 31st March 2020. Subjects with twin pregnancies were excluded from the study. The validated Arabic NorVold Domestic Abuse Questionnaire (NORAQ) was used to determine the prevalence of emotional and physical domestic violence. The recruited subjects were re-evaluated for birth outcomes at 2– 4 weeks postpartum.Results: A total of 960 women participated in the study, with the mean age of 30.3 ± 5.4 years. Overall, experiences of lifelong domestic violence were reported by 161 women (16.8%), and the prevalence rate declined substantially in the one-year period preceding pregnancy and during pregnancy, 2.7% and 1.6%, respectively. Women who reported any type of domestic violence one year before pregnancy were at a higher risk of experiencing it again during pregnancy. A multivariate analysis of the obtained data revealed a strong association between physical domestic violence one year before pregnancy and unplanned pregnancy. Subjects with lifelong domestic violence reported higher rates of depression, insomnia, and somatic symptoms. No significant association was found between domestic violence, across any periods, and birth outcomes.Conclusion: The rates of domestic violence are relatively lower during pregnancy and one year before pregnancy compared to those of the lifelong period among Omani women. A significant association was found between domestic violence and depression, insomnia, somatic symptoms, and unplanned pregnancy. Screening for domestic violence during the perinatal period, using high-quality surveys, is of utmost importance.Keywords: domestic violence, women, pregnancy, risk factors, birth outcomes, Oman